The Relationship Between Nutritional Status and Menarche Cycle in Students - Ida Nuraida; Yayuk Sri Rahayu; Nura Suciati; Devia Lydia Putri (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Menstruation is periodic bleeding from the uterus that begins about 14 days after ovulation periodically due to the shedding of the lining of the uterus. Generally, the menarche cycle in normal women is 28-35 days and the duration of menstruation is between 3-7 days. The menarche cycle in women is said to be abnormal if the menarche cycle is less than 21 days or more than 40 days. Irregular menarche cycles can be caused by irregular eating patterns and unbalanced nutrition. The purpose of this research was to determine the relationship between nutritional status and the menarche cycle in female students. This type of research is quantitative research with a cross sectional approach. This type of research is quantitative research with a cross sectional approach. The sampling technique in this study was random sampling with a total sample of 51 female students who had been counted from a total population of 104 female students. Data processing uses univariate data analysis using a frequency distribution, while bivariate uses the Chi Square test. Most of the respondents had normal nutritional status, amounting to 66.7%, and respondents who had abnormal nutritional status amounted to 33.3%. Most of the respondents experienced regular menstruation as much as 70.6%, most of them experienced irregular menstruation as much as 29.4%. The statistical test results between nutritional status and the menarche cycle obtained a P value of 0.012 or a Pvalue <0.005, which means that there is a relationship between nutritional status and the menarche cycle. Nutritional status can affect the menarche cycle so there is a need to improve nutrition for female students.Keywords: Menarche cycle, Nutrition, Student